MERGERS AND ACQUISITION OF FINANCIAL INSTITUTIONS IN NIGERIA: A CASE STUDY OF INSURANCE COMPANY - Akinwale, Samson O (Archives of Business Research, 2018)
The new racialization directive by National Insurance Commission (NICOM) were aimed to strengthening the capital base of Nigerian Insurance Companies. The new risk based supervision model (RBSM) ultimately revolutionize the operations of the entire Industry for efficient and effective performance of the Nigerian Insurance Industry. The new requirements will engender business stabilization which will outlaw the prevailing situation where every insurance company underwrites all manners of risks even when financially unfit for them. One of the measure put in place to achieve this are Mergers and acquisitions. Bigger companies were encouraged to buy smaller ones while the smaller ones put up themselves for acquisition. This article presents the methods, process and the technicalities involved in Mergers and acquisitions in the Nigeria Insurance Industry